The eels of the genus Nettenchelys, with description of a new species from Taiwan (Teleostei: Anguilliformes: Nettastomatidae) - Smith, David G.; Lin, James; Chen, Hong-Ming; Pogonoski, John J. (Zootaxa, 2015)
The species of the genus Nettenchelys are summarized. Nine species are recognized on the basis of adult specimens: Nettenchelys dionisi Brito, N. erroriensis Karmovskaya, N. exoria Böhlke & Smith, N. gephyra Castle & Smith, N. inion Smith & Böhlke, N. paxtoni Karmovskaya, N. proxima new species, N. pygmaea Smith & Böhlke, and N. taylori Alcock. Another species, N. bellottii (D’Ancona) is based on a larva. Nettenchelys gephyra is redescribed on the basis of additional specimens from northeastern Taiwan, Indonesia and Australia. Nettenchelys proxima new species is described from a specimen from southwestern Taiwan. Nettenchelys sp. reported by Uyeno & Sasaki (1983) is found to be a specimen of Facciolella. Information on larvae is updated based on new knowledge of the genus.